TINJAUAN AKUNTANSI TERHADAP FITUR-FITUR PRIORITAS GENERASI MILENIAL DALAM MEMILIH BANK - Fongnawati Budhijono; Olivia Nainggolan (Jurnal Bina Akuntansi, 2020)
This study aims to explore the features of the millennial generation's concern inchoosing banks from an accounting review. Data obtained through a survey of 118respondents belonging to millennial generation in several cities in Indonesia who arecustomers of certain banks using Google forms and questionnaires with closed choices.Sampling was done by purposive sampling technique. Data analysis was performedwith central tendency and Contingency Table Analysis. It was found that the Bank'sReputation, Availability of ATM Machines, and Reliable M-Banking Facilities were 3bank features that were a priority for millennial generation in bank selection. Theresearch findings do not indicate that millennial customers directly empoweraccounting information in determining bank selection based on the features theychoose. It was found that there was a relationship between gender with factors thatwere the 3 highest priorities of respondents in deciding to choose a particular bank.There is no relationship between the area of origin with factors that are the 3 highestpriorities of respondents in deciding to choose a particular bank.